Since there are 5,280 feet in one mile and 3.3 feet in one meter, how many meters per second are equivalent to 60 miles per hour?a.) 26 (2)/(3) meters per second
b.) 198 meters per second
c.) 266 (2)/(3 (2)/(3) ) meters per second
d.) 290 (2)/(5)
please explain.

Answers

Answer 1
Answer: Given:
1 mile = 5280 feet
1 meter = 3.3 feet

convert 60 miles per hour to meters per second

60 miles to meters

60 miles x 5280ft x 1meter = (60*5280m)/3.3 = 316800m/3.3
                  1 mile    3.3ft
= 96,000 meters

1 hour to seconds

1 hour x 60 minutes x 60 seconds =   1 * 60 * 60sec = 3600 seconds 
                1 hour            1 minute

unit rate: meters per second

96000 meters ÷ 3600 seconds = 26 2400/3600 
simplify 26 2400/3600 ⇒ 26 2/3 meters per second

2400 ÷ 1200 = 2
3600 ÷ 1200 = 3

Related Questions

Katrina is building a deck. She cuts 3 lengths of wood from a 72-inch board. The first length is 30 3/4 inches. The second length is 12 1/4 inches. And the third length is 16 1/4 inches. How much of the original board remains after Katrina makes her cuts?
barista alex is crafting a new coffee blend. he combines two coffee beans: bean a, which has a bitterness level of 25%, and bean b, which has a bitterness level of 75%. to create his signature blend, he wants a 1000g batch with a bitterness level of 40%. how much of each coffee bean should he use?
1. Refer to the equation 3x − 5y = 15. (a) Create a table of values for at least 4 points. Show your work on how you found the values for each coordinate pair, and validated the points were on the line. Work for Point 1 Work for Point 2 Work for Point 3 Work for Point 4
What doubles fact can help you solve 6+5=11?
This is hard for me, can someone please help? Loren solved the equation 10 = StartFraction 19 Over 9 EndFraction (149) + b for b as part of her work to find the equation of a trend line that passes through the points (1, 130) and (10, 149). What error did Loren make? She should have solved 10 = StartFraction 9 Over 19 EndFraction (149) + b for b. She should have solved 1 = StartFraction 19 Over 9 EndFraction (130) + b for b. She should have solved 149 = StartFraction 19 Over 9 EndFraction (10) + b for b. She should have solved 130 = StartFraction 9 Over 19 EndFraction (1) + b for b.

Multiplies to -0.72 and adds to 0.6

Answers

Multiplies to -0.72 =  - 0.6 * (1.2).

Adds to 0.6  =   

-0.6 + (1.2) = 1.2 - 0.6 = 0.6.

Hence the two numbers are -0.6 and 1.2.

Given a = {1, 3, 5}, b = {2, 4, 6} and c={1, 2, 3, 4, 5, 6}, then a ∪ (b ∩
c. =

Answers

Match the following. Given A = {1, 2, 3, 4, 5} B = {2, 4, 6} C = {1, 3, 5}?1. A ∪ B __ {1, 2, 3, 4, 5} 
2. A ∪ C __ null, or empty set 
3. A ∩ B __ {1, 3, 5} 
4. A ∩ C __ {1, 2, 3, 4, 5, 6} 
5. B ∩ C __ {2, 4}

Final answer:

The result of a ∪ (b ∩ c) equals the union of set a with set b, since set b is completely contained within set c. The final answer is {1, 2, 3, 4, 5, 6}.

Explanation:

The question involves concepts of set theory and specifically deals with the union and intersection of sets. The sets given are a = {1, 3, 5}, b = {2, 4, 6}, and c = {1, 2, 3, 4, 5, 6}. We're asked to find the result of a ∪ (b ∩ c), which means we want to determine the union of set a with the intersection of sets b and c. First, we need to find b ∩ c, which are the elements common to both b and c. Since c contains all the elements of b, the intersection b ∩ c is simply b, which is {2, 4, 6}. Now, we take the union of set a with this result, so a ∪ (b ∩ c) = a ∪ b = {1, 2, 3, 4, 5, 6}. Hence, a ∪ (b ∩ c) contains all elements from both set a and set b, as there were no common elements in set a and set b originally.

Learn more about Union and Intersection of Sets here:

brainly.com/question/23337676

#SPJ2

The sum of 3 consecutive integers is 90. find the largest integer if x is the smallest integer

Answers

Well, you get x+(x+1)+(x+2)=90 or 3x+3=90, 3x=87 or x=29. x+2=31, the largest one.

Answer:

The largest integer is x+2, or 31.

Talia wants to write the equation of the graphed line in point-slope form. These are the steps she plans to use: Step 1: Choose a point on the line, such as (2, 5).
Step 2: Choose another point on the line, such as (1, 3).
Step 3: Count units to determine the slope ratio. The line runs 1 unit to the right and rises 2 units up, so the slope is.
Step 4: Substitute those values into the point-slope form. y – y1 = m(x – x1) y – 3 = (x – 1) Which of Talia’s steps is incorrect? Step 1 is incorrect because it uses a point that is not on the line. Step 2 is incorrect because it uses a point that is not on the line. Step 3 is incorrect because it shows an incorrect ratio of the slope.
Step 4 is incorrect because it shows an incorrect substitution of (1, 3) into the point-slope form

Answers

From the steps Talia chooses to find the equation of the line, we shall evaluate the incorrect step as follows:
Step 1:
Choose a point in the line such as (2,5)
Step 2:
Choose another point on the line, such as (1, 3)
step 3:
Count units to determine the slope ratio. The line runs 1 unit to the right and rises 2 units up, so the slope is. 
(5-3)/(2-1)=2/2=1
step 4:
 Substitute those values into the point-slope form
y-y1=m(x-x1)
y-3=2(x-1)
y=2x+1
Thus the answer is:
Step 4 is incorrect because it shows an incorrect substitution of (1, 3) into the point-slope form

just took the test the right answer is step 3 is incorrect

I'll give 100 pts and brainliest if you answer this!!!thank you for the help boo

Perform the operation. Write the answer in standard form.
1. (6 − i) + (9 + 5i)
2. (7 + 3i) + (11 + 2i)
3. (12 + 4i) − (2 − 15i)
4. (3 − 7i) − (3 + 5i)
5. 7 − (2 − 3i) + 6i
6. −16 + (3 + 4i) − 4i
7. 3i(6 − 5i)
8. −2i(8 + 2i)
9. (−5 + i)(8 − 6i)
10. (3 − 6i)(−1 + 7i)
11. (2 + 5i)(2 − 5i)
12. (−3 − i)(−3 + I)
13. (4 + i) 2
14. (5 − 9i) 2
Thank you again <3

Answers

Answer:

1. 4i+15

2. 5i+18

3. -11i+10

4. -2i

5. 9i+5

6. -13

7. -15i^(2)+18i

8. -4i^2-16i

9. -6i^2+38i-40

10. -42i^2+27i-3

11. -25i^2+4

12. -i^2+9

13. 2i+8

14. -18i+10

Step-by-step explanation:

Standard form means to put the terms in order based on their exponent (x³ -> x² -> x -> constant)

1. (6 - i) + (9 + 5i)

4i+15

2. (7 + 3i) + (11 + 2i)

5i+18

3. (12 + 4i) - (2 - 15i)

-11i+10

4. (3 - 7i) - (3 + 5i)

-2i

35i^2+6i-9

5. 7 - (2 - 3i) + 6i

7 - 2 + 3i + 6i

9i+5

6. -16 + (3 + 4i) - 4i

-16 + 3 + 4i - 4i

-13

7. 3i(6-5i)

18i-15i^2

-15i^2+18i

8. -2i(8+2i)

-16i+-4i^2

-4i^2-16i

9. (-5 + i)(8 - 6i)

-40+30i+8i-6i^2

-6i^2+38i-40

10. (3 - 6i)(-1 + 7i)

-3+21i+6i-42i^2

42i^2+27i-3

11. (2 + 5i)(2 - 5i)

4-10i+10i-25i^(2)

-25i^2+4

12. (-3 - i)(-3 + i)

9 -3i + 3i -i^2

-i^2+9

13. (4 + i) * 2

2i+8

14. (5 - 9i) * 2

-18i+10

:p when I first started answering this I thought the parentheses were being multiplied every time and did 100x more work .-.

Hope it helps <3 :D

Solve the conjunction and describe the solution set. -5 ≤ 3m + 1 < 4

A: m ≥ -2 and m < 1
B: m ≤ -2 or m > 1
C m ≥ -4/3 and m < 5/3
D: m ≥ - 4/3 or m < 5/3

Answers

 -5 ≤ 3m + 1 < 4
- 1           - 1  - 1
 -6 ≤ 3m < 3
  3      3     3
 -2 ≤ m < 1

Solution Set: {m|-2 ≤ m < 1}, {m|m ≥ -2 and m < 1}, [-2, 1)

The answer is A.

Final answer:

The solution to the conjunction -5 ≤ 3m + 1 < 4 is m ≥ -2 and m < 1.

Explanation:

To solve the conjunction -5 ≤ 3m + 1 < 4, we need to solve the two inequalities separately. Starting with the left inequality: -5 ≤ 3m + 1. We subtract 1 from both sides: -6 ≤ 3m. Dividing both sides by 3, we get: -2 ≤ m. Next, we solve the right inequality: 3m + 1 < 4. We subtract 1 from both sides: 3m < 3. Dividing both sides by 3, we get: m < 1. Therefore, the solution to the conjunction is m ≥ -2 and m < 1. This means that m is greater than or equal to -2, but less than 1.

Learn more about Solving inequalities here:

brainly.com/question/26855203

#SPJ2